The Design of Intervention among Survivors of Disaster - Siti Urbayatun; Erlina Listyanti Widuri; Ani Muttaqiyatun; Dewi Eskawati (International Journal of Public Health Science (IJPHS), 2014)
Indonesia is a region that is frequently hit by disasters, especially the earthquake because of geological factors. Earthquake in 2006 in the region of Yogyakarta and Central Java still has problems to this day, the basics of the economy has not fully recovered , disabled people coud not work as usual, people experience a variety of stressors such as income and material stress and emotional stress. The aimed of this study was to find out the effect of cognitive and religious intervention to cope with stress of disaster. The subjects of this study were people in Bantul who exposed to stress due to disasters such as disability and individuals who have low self-confidence because of disabilty. The method of the study was a responsive action research. Data were collected through observation, interviews, focus group discussions, psychoeducation and training. The study found that cognitive and religious intervention has positive impact on recovery of the subject, for example increase on self-confidence of individual and decrease in the mean of SUD (subjective unit disturbances) score of familie’s subject member. The interventions were usefull to improve the future intervention of disabled persons and people who experience stress of family member’s disability.